Transposition of Drupadi in Garin Nugroho's Setan Jawa: Woman as a Javanese Symbolic Act - Kusuma Dewi, Agustina; Piliang, Yasraf Amir; Irfansyah, Irfansyah; Saidi, Acep Iwan (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2020)
Art film is a film full of symbols. The film Setan Jawa by Garin Nugroho (2016) brings the concept of a silent film and the cinematic-orchestral collaboration with various standards across arts, while also adapts some cultural narratives in the Javanese context. This film presents Drupadi narrative, one of the Javanese Wayang cultural narratives. Drupadi is often referred to as a symbol of women’s loyalty and obedience to the universal law, through her obedience to her husband and mother, although this obedience is contrary to the self (I) concept. With the help of textual analysis, this article aims to identify the adaptation of Drupadi’s cultural narrative that is creatively transposed in the film Setan Jawa. The results show that there is a director’s personal code (idiolect) in the film, that offers women’ representation different from the conventions in the Javanese culture. While the conclusion might be arguable, one can reflect on the symbolic act of women’s representation being creatively transposed not as subordinate but as having the power to fulfill their own destiny.